Literature Review Pemberian Aromaterapi Lemon Terhadap Penurunan Skala Nyeri Luka Perineum Post Partum - Losu, Fredrika Nancy; Tuju, Sjenni Olga; Toliango, Trisna; Manueke, Iyam; Lumy, Freike N. (POLTEKKES KEMENKES MANADO, 2023)
Background: Spontaneous vaginal birth risks the mother receiving perineal stitches due to episiotomy and spontaneous tearing. Each individual's pain response is unique and relatively different. Overcoming pain can be done pharmacologically using analgesics and non-pharmacological methods including skin stimulation strategy methods, sensory stimulation strategies and cognitive strategies. Various types of aromatherapy are jasmine, lemon, ginger, jasmine, rose, cinnamon, lavender. Objective: To achieve the effectiveness of aromatherapy intervention in reducing the pain scale of postpartum perineal wounds. Method: Search for research articles in several databases using certain keywords in the 2016-2022 period. The search results obtained 7 articles using midwifery interventions, 7 articles that met the inclusion criteria. There were 7 articles included in the category so they were good for further analysis. Critical analysis of 7 articles was carried out based on design, population and sample, sampling, treatment, parameters, findings and conclusions. Results : Literature review shows that current aromatherapy interventions in the form of complementary health services vary greatly in terms of methods, components, duration, individuals involved, specificity and effectiveness. Statistical analysis shows that all of these methods have resulted in a significant reduction in the pain scale of postpartum perineal wounds, recommendations for health workers to take special training beforehand and have competence in administering measures to reduce the pain scale of postpartum perineal wounds.